Youth as stakeholders and their engagement towards government programmes (GP) - Faridah Ibrahim,; Siti Maziha Mustapha,; Amli Hazlin Ahmad Mokhtar,; Dil Froz Jan Sayed Halem Shah,; Koh, Suet Nie (Penerbit Universiti Kebangsaan Malaysia, 2019)
The study looks into youth as Stakeholders and their engagement in government programmes. The implementation of programmes by a country, government or company will generate fruitful outcomes if the plans and programmes are well received by the stakeholders. Stakeholders are both internal and external. However, the focus of this study is the external stakeholders namely the citizens of this country with specific focus on youth. In the context of Malaysia, generally government programmes are implemented with the aim of improving the quality of life of the people. This study is carried out using focus group discussions (FGD). It presents the findings from the FGD focussing on the young adults of different ethnics. The research questions aimed to answer the following: What are the government programmes identified by the stakeholders? What are the reactions of the stakeholders toward the identified programmes? And to what extent do the stakeholders engage in the identified programmes? From the FGD, it was found that stakeholders identified government programmes from five sectors namely housing projects, transportation, healthcare, education and financial support. Several stakeholders reacted positively toward the benefits of the programmes, however they had negative reactions on certain programmes. Some stakeholders stressed that regardless of the positive and negative aspects of the government programmes, they monitored and showed concern on the effectiveness of the programmes implemented. This is evidence of how engaged youth were in the government programmes. Recommendations were offered by the stakeholders for successful implementation of current and future government programmes.